INNOVATIVE RISK LEADERSHIP IN AVIATION industry insights and cases. - Flouris, Triant G. (ROUTLEDGE, 2025)
This book focuses on the perspective of risk leadership strategy in view of human resources, diversity management and inclusion projects in the multicultural business environment of aviation operations. It will enable the reader to successfully develop strategies and manage their sustainability with sound risk leadership, organisational behaviour, and ergonomic-focused approaches, to achieve corporate objectives within their aviation industry context.Innovative risk leadership is the essential driver in diversity, ethical, and inclusion-based global management strategies which are affected by digitalisation and artificial intelligence (AI). This book showcases many contemporary management issues grounded in the innovative risk leadership concept and will serve as a useful resource for managers and professionals as well as researchers of enterprise management and strategy. It examines the successful integration of innovative risk leadership into business management with diversity and inclusion shaped by AI with an emphasis on aviation issues, recognising that aviation enterprises operate in a hypercompetitive environment, applying digital technologies to achieve smooth operations and efficient performance, and that the effective management of multiculturalism is a key priority in this global industry. Such realities result in higher risk and as such aviation managers must always strive to find ways to mitigate this risk. Practices and policies that the aviation industry applies to handle these issues are shown to be adopted from other sectors as well as adapted to other sectors.Written for aviation industry managers, professionals, students, and researchers interested in risk management, the book could also be utilised as a handbook for MROs, airlines, airports, and aerospace manufacturers.
Keywords: Airlines -- Risk management.; Airlines -- Management.; Diversity in the workplace.; elektronické knihy; electronic books